CHARACTERISTICS OF NANOCREAM SUNSCREEN COMBINING KEPOK BANANA CORM AND RED WATERMELON MESOCARP - Andini; Anggraeni In Oktavia; Reyhana Salwa; Salsabila Putri (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Plant parts deemed as waste, such as banana corm and watermelon mesocarp, show promise as raw materials for cosmetics when processed using nanocream technology. This study aimed to assess the characteristics of nanocream creams combining these extracts. The characterization of the nanocream creams included organoleptic testing, homogeneity testing, pH testing, nanocream type testing, spreadability testing, stability testing, viscosity testing, antioxidant activity testing using the DPPH method, and sunscreen activity evaluation through SPF determination using UV-Vis spectrophotometry. The research results show that the organoleptic properties of all formulations are semi-solid, with a white to yellowish color. The type of cream for all formulations is oil-in-water, and homogeneous. The pH values for FI, FII, and FIII are 6.37, 6.2, and 6.2, respectively (pvalue=0.017), the spreadability values are 5.94, 5.72, and 5.64 respectively (p=0.024), the viscosity values are 5635, 5339, and 5181, respectively (p<0.05), the antioxidant activity is indicated by IC50 values of 66.39, 24.50, and 56.45 respectively, while the SPF values are 0.95, 0.87, and 1.01 repectively. The resulting nanocream demonstrate favorable organoleptic characteristics, pH, homogeneity, spreadability, and viscosity meeting the required standards, with the highest antioxidant activity observed in FII and no significant sunscreen potential in any of the formulations.